PKM Inovasi Pengolahan Tahu - Hikmayani Subur; Septiannisa Paramita; Abdul Rajab; Irwandi Irwandi; Wahyu Muh. Syata (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
This community service activity aims to introduce food product innovation through the processing of tofu into Mozzarella Tofu as an effort to increase the economic value of local food ingredients and encourage community entrepreneurial skills. This activity was carried out through mentoring and guidance to participants in Bungoro District, Pangkajene and Kepulauan Regency for two weeks. The activity stages included an introduction to tools and materials, an explanation of the manufacturing process, hands-on practice of making Mozzarella Tofu, and an evaluation of the product results. The results of the activity showed that tofu can be developed into a more attractive, practical, and marketable food product by combining it with mozzarella cheese. This product has a savory taste, soft texture, and a melted cheese sensation that can attract the interest of consumers from various groups. In addition, the marketing strategy was designed using the 4P concept, namely product, price, place, and promotion, with direct sales and promotions through social media such as WhatsApp, Facebook, and Instagram. This activity implies that simple food innovations based on local food ingredients can increase creativity, entrepreneurial skills, and opportunities for developing culinary businesses in the community.